Reliability and usefulness of time-motion and physiological responses in simulated judo matches - Franchini, E.; Dunn, E.; Takito, M. Y. (The Journal of Strength and Conditioning Research, 2020)
Match simulations have been used to investigate different interventions in judo. However, no study has assessed the reliability of actions performed and the physiological responses to the match and its usefulness. Thus, 2 studies were conducted to verify the reliability of time-motion and physiological responses to judo matches. In the first study, 25 judo athletes performed one 5-minute judo match simulation twice, 1 week apart, and had their heart rate and blood lactate measured. In the second, 12 judo athletes performed one 5-minute judo simulation 4 times, 72 hours apart, and had their primary actions and match temporal structure analyzed. Comparisons between conditions, reliability (using intraclass correlation coefficient, ICC), typical error (TE), smallest worthwhile change (SWC), and minimal detectable change were determined. The main findings indicated that: (a) there were no differences between matches for any variable; (b) ICCs were significant (except for blood lactate before matches in both studies) with 6 variables presenting large (number of attacks plus defensive actions, number of scoring actions, efficiency, number of sutemi-waza, time per combat sequence, and time per interval phase time), and the remaining 15 variables presenting very large reliability; (c) TE was higher than SWC for all variables when small differences were considered. Moderate changes in peak blood lactate and the change in blood lactate (in both studies), and time in tachi-waza could be properly detected; however, only large changes could be detected for all other variables, suggesting that investigations using match simulation as an outcome variable may only detect large changes.